β-Secosterol, an Oxyphytosterol Produced Through the Reaction of β-Sitosterol with Ozone, Demonstrates Different Cytotoxic Effects on BRL-3A and HTC Cells - Bianca S. Takayasu; Igor R. Martins; Miriam Uemi; Janice Onuki; Glaucia M. Machado-Santelli (Biomolecules)
Sitosterol (Sito) is a phytosterol with bioactive properties, including reducing atherosclerosis risk and anti-inflammatory and antitumoral effects. However, it can be oxidized by reactive oxygen species such as ozone (O3), producing oxyphytosterols with harmful effects such as cytotoxicity, oxidative stress, and proatherogenicity. Ozone, a strong oxidant and common pollutant, can alter plant steroid compounds, raising concerns about dietary oxyphytosterol intake. Studies identify β-Secosterol (βSec) as the primary ozone-derived oxyphytosterol from Sito, exhibiting cytotoxic effects on HepG2 human liver tumor cells. This study investigated βSec’s biological effects on two rat liver cell lines: BRL-3A (immortalized) and HTC (tumoral), examining cell death, cell cycle progression, morphology, and cytoskeleton organization. While Sito influenced cell metabolic activity without affecting cell survival or morphology, βSec demonstrated significant cytotoxicity in both cell lines. It induced G0/G1 cell cycle arrest and disrupted cytoskeleton organization, with different implications: BRL-3A cells showed persistent cytoskeletal changes potentially linked to tumor induction, while HTC cells displayed chemoresistance, restoring cytoskeletal integrity and enhancing metastatic potential. These findings reveal βSec’s complex, context-dependent effects, suggesting it may promote tumor-like behavior in non-tumoral cells and resistance mechanisms in cancer cells, contributing to understanding oxyphytosterols’ implications for physiological and pathological conditions.